2006
DOI: 10.1373/clinchem.2006.080366
|View full text |Cite
|
Sign up to set email alerts
|

Prealbumin Serum Concentrations as a Useful Tool in the Assessment of Malnutrition in Hospitalized Patients

Abstract: Background: Protein-energy malnutrition (PEM) is a common condition among patients admitted to hospitals, and it is associated with a worse prognosis and increased mortality. Although several screening systems have been developed, PEM is still poorly recognized, and there is no consensus on which test is more reliable and feasible in clinical practice. Prealbumin (PAB) is a potential useful PEM marker because its serum concentrations are closely related to early changes in nutritional status. Methods: We studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
116
0
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(133 citation statements)
references
References 23 publications
5
116
0
12
Order By: Relevance
“…In our study, prealbumin levels showed a more gradual decline with increasing NRS as compared with serum albumin levels. Similar to serum albumin and retinolbinding protein, prealbumin levels are influenced by systemic inflammatory diseases, limiting their use in acutely ill patients (Lopez-Hellin et al, 2002;Devoto et al, 2006). This might explain why prealbumin levels in our study declined with increasing NRS scores, which were more influenced by comorbidities compared with the MNA score.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In our study, prealbumin levels showed a more gradual decline with increasing NRS as compared with serum albumin levels. Similar to serum albumin and retinolbinding protein, prealbumin levels are influenced by systemic inflammatory diseases, limiting their use in acutely ill patients (Lopez-Hellin et al, 2002;Devoto et al, 2006). This might explain why prealbumin levels in our study declined with increasing NRS scores, which were more influenced by comorbidities compared with the MNA score.…”
Section: Discussionmentioning
confidence: 73%
“…However, its function in nutritional screening and in predicting mortality is controversial (Ferguson et al, 1993;Brugler et al, 2002;Langkamp-Henken et al, 2005;Devoto et al, 2006;Carriere et al, 2008). Robinson et al (2003) found prealbumin to be a significant predictor of malnutrition, whereas serum albumin and retinol-binding protein were not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the reference method, 41% of subjects had mild malnutrition and 19% suffered from severe malnutrition. Prealbumin showed the best agreement with the standard method and a good profile of sensitivity and specificity, compared with SGA and Prognostic Inflammatory and Nutritional Index, and could be used as a practical and valid method of assessing malnutrition (46). In summary, several studies show the benefit of some nutritional risk score over others, but many suggest the combined use of these tools along with determining prealbumin levels, which is the reason why we also chose this approach in our study.…”
Section: Discussionmentioning
confidence: 84%
“…A pré-albumina, por ter uma meia-vida mais curta do que a albumina, é apontada como marcador mais sensível para detectar desnutrição 24 , contudo o alto custo do exame dificulta o seu uso de rotina. Por outro lado, ambos indicadores podem estar alterados em algumas doenças crônicas podendo mascarar os verdadeiros resultados 25 .…”
Section: I S C U S S ã Ounclassified